PENGEMBANGAN MODEL PEMBELAJARAN JARAK JAUH BERBASIS WEB - Atmoko Nugroho (Jurusan Teknologi Informasi Universitas Semarang, 2012)
Process to learn usually used study concept conventionally, where educative participant and educator earn meeting each other in an certain time and place. But performed within this research non conventional study, study used by this model study of long distance, anywhere its place there is no problem, during study items and evaluation there is still study will be. Target of in this research is to wear media of web as medium study of long distance by wearing concept of elearning. Research method the used is reengineering, while its development method wear ADDIE ( Analysis, Desaign, Development, Implementation And Evaluation) while for the method of desain wear UML ( Unified Modelling of Language). Result of research can be accessed by online, comprising items, assessment and evaluation.